How to brand a border despite its wall? A social semiotics approach to cross-border place branding. Issue 135 (October 2022) - Sohn, Christophe
Highlights: Borders represent semiotic resources for cross-border place branding. Two meaning-making strategies are distinguished within a conceptual framework. Border assets can be valorized for the branding of a cross-border place. Borders can also be invisibilized to legitimize a seamless cross-border place. The more the border is militarized, the more selective the image of the region. Abstract: This paper explores the ways in which borders are likely to be used as a semiotic resource in cross-border place branding. We develop a conceptual framework, distinguishing two meaning-making strategies: one that seeks to valorize borders as assets for cross-border place branding and another that relies on their invisibilization in order to promote, implicitly, the legitimacy of a seamless cross-border regional imaginary. For each meaning-making strategy, specific border discourses are identified. Based on a social semiotics approach, we analyze the case of Cali Baja, a place branding initiative that seeks to promote a bi-national mega-region straddling the US-Mexico border between San Diego and Tijuana. Despite the militarization of the border and the highly visible physical wall that divides Cali Baja, a selective branding discourse framed around favorable border images and representations is brought to the fore. It is therefore at the cost of the partial (in)visibilization of the border that the mega-region can be given value and promoted on the international scene, but it is also the discrepancy with the identity of the bi-national region that precipitated the failure of this place branding initiative.